Harmonious relations: Quality transmission among composers in the very long run - Karol Jan Borowiecki; Nicholas Ford; Maria Marchenko (European Historical Economics Society (EHES), 2022)
Most creatives acquire professional talents by learning from others, but in most settings it is difficult to estimate the existence of long-term effects. This paper explores the transmission of skills over a period of more than seven centuries by focusing on the case of music composers. We ask the question: how does a composer's quality influence the quality of the composers he or she teaches? Our analysis builds on a unique dataset of 17,433 composers from around the world since the fourteenth century. By comparing actual teacher-student pairs with plausible counterfactual pairs and by using a two-stage framework, we show a strong effect of quality transmission. Moreover, we find quality transmission persists across multiple generations: from teacher to student, and subsequently to student's student and so on. Our results provide new insights on drivers of creativity over the very long term, as well as the influence of teachers on students' achievements.
Keywords: I21; J24; N30; O31; Z11; D31; D72; H20; N43; N93; P48; 330; creativity; transmission of ideas; music history; teacher influence